Cardiopulmonary exercise testing and impedance cardiography in the assessment of exercise capacity of patients with coronary artery disease early after myocardial revascularization - Małgorzata Kurpaska; Paweł Krzesiński; Grzegorz Gielerak; Karina Gołębiewska; Katarzyna Piotrowicz (BMC, 2022)
Abstract Background Patients with coronary artery disease (CAD) are characterized by different levels of physical capacity, which depends not only on the anatomical advancement of atherosclerosis, but also on the individual cardiovascular hemodynamic response to exercise. The aim of this study was evaluating the relationship between parameters of exercise capacity assessed via cardiopulmonary exercise testing (CPET) and impedance cardiography (ICG) hemodynamics in patients with CAD. Methods Exercise capacity was assessed in 54 patients with CAD (41 men, aged 59.5 ± 8.6 years) within 6 weeks after revascularization by means of oxygen uptake (VO2), assessed via CPET, and hemodynamic parameters [heart rate (HR), stroke volume, cardiac output (CO), left cardiac work index (LCWi)], measured by ICG. Correlations between these parameters at anaerobic threshold (AT) and at the peak of exercise as well as their changes (Δpeak-rest, Δpeak-AT) were evaluated. Results A large proportion of patients exhibited reduced exercise capacity, with 63% not reaching 80% of predicted peak VO2. Clinically relevant correlations were noted between the absolute peak values of VO2 versus HR, VO2 versus CO, and VO2 versus LCWi (R = 0.45, p = 0.0005; R = 0.33, p = 0.015; and R = 0.40, p = 0.003, respectively). There was no correlation between AT VO2 and hemodynamic parameters at the AT time point. Furthermore ΔVO2 (peak-AT) correlated with ΔHR (peak-AT), ΔCO (peak-AT) and ΔLCWi (peak-AT) (R = 0.52, p < 0.0001, R = 0.49, p = 0.0001; and R = 0.49, p = 0.0001, respectively). ΔVO2 (peak-rest) correlated with ΔHR (peak-rest), ΔCO (peak-rest), and ΔLCWi (peak-rest) (R = 0.47, p < 0.0001; R = 0.41, p = 0.002; and R = 0.43, p = 0.001, respectively). Conclusion ICG is a reliable method of assessing the cardiovascular response to exercise in patients with CAD. Some ICG parameters show definite correlations with parameters of cardiovascular capacity of proven clinical utility, such as peak VO2.